TEACHER'S QUESTIONS OF THINKING SKILLS IN AN ENGLISH AS FOREIGN LANGUAGE CLASSROOM - Feby Dwi Putri Setyo Setyo; Suprihadi Suprihadi; Fajar Kartika Kartika (Universitas Muria Kudus, 2022)
Effective teachers’ questioning is very important in controlling the classroom interaction, focusing students’ learning in the lesson, making the students be more active and motivated to hold their opinion. The objectives of this descriptive qualitative research are to find out the types of question used by the teacher and to describe the questioning purposes used by the teacher. The researchers collected the teacher’s questioning by doing observation and taking audio recording and note-taking. The first step in analyzing data is classifying the teachers’ questions and the purposes of questioning and then drawing the conclusions. The results of this research show that the dominant type of question used by the English teacher is remembering. Most of the teacher’s thinking skill questions are LOTS instead of HOTS. Meanwhile, the dominant purpose of questioning is guiding the students to focus on the learning and to understand the material. The researchers suggest that the teachers use variety of questions not only for managing the class but also to focusing and motivating the students to express their opinion and be more active in the classroom and to developing students’ HOTS.